2020
DOI: 10.3390/plants9121641
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas putida Represses JA- and SA-Mediated Defense Pathways in Rice and Promotes an Alternative Defense Mechanism Possibly through ABA Signaling

Abstract: The signaling pathways induced by Pseudomonas putida in rice plants at the early plant–rhizobacteria interaction stages, with and without inoculation of Xanthomonas oryzae pv. oryzae, were studied. In the absence of pathogen, P. putida reduced ethylene (ET) production, and promoted root and stem elongation. Interestingly, gene OsHDA702, which plays an important role in root formation, was found significantly up-regulated in the presence of the rhizobacterium. Although X. oryzae pv. oryzae inoculation enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The role of gibberellins under saline conditions is also associated with mitigating the deleterious effects of salt stress by increasing water availability to plants (Colebrook et al 2014 ). Recently, it was reported that inoculation of rice plants with P. putida KT2440 stimulates an alternative plant defense mechanism based on abscisic acid accumulation (Wang et al 2020a , b ).…”
Section: Plant Growth Promotion Activities and Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of gibberellins under saline conditions is also associated with mitigating the deleterious effects of salt stress by increasing water availability to plants (Colebrook et al 2014 ). Recently, it was reported that inoculation of rice plants with P. putida KT2440 stimulates an alternative plant defense mechanism based on abscisic acid accumulation (Wang et al 2020a , b ).…”
Section: Plant Growth Promotion Activities and Traitsmentioning
confidence: 99%
“…The best studied Pseudomonas PGPR strains include the P. fluorescens complex (including P. protegens , P. chlororaphis , P. brassicacearum , and P. koreensis ) (Ashraf et al 2019 ; Kang et al 2021 ; Wang et al 2020a , b ; Zhang et al 2020 ), P. stutzeri (Lami et al 2020 ), and P. putida (Costa-Gutierrez et al 2020a ; 2020b ). Despite the large number of reviews about Pseudomonas strains (e.g., Bhimeshwari et al 2018 ; Nadeem et al 2016 ; Shaikh et al 2020 ), the role of P. putida as a plant growth promoter has been neglected in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, endophytic bacteria can initiate ISR using pathways mediated by salicylic acid, jasmonic acid, and ethylene (Yanti et al, 2019). Salicylic acid signaling positively regulates plant defense against biotrophic plant pathogenic fungi, whereas jasmonic acid and ethylene pathways are commonly required for resistance to necrotrophic plant pathogenic fungi and pests (Wang et al, 2020a). However, endophytic bacteria can use distinct plant defense signaling pathways, depending on the type of phytopathogen invader, that is, the same bacterium could use different pathways to confer resistance to different pathogens (Afzal et al, 2019).…”
Section: Indirect Plant Growth Promotionmentioning
confidence: 99%